Synthesis, structure and reactions of an amidinate stabilised trigallane - Linti, Gerald W.; Zessin, Thomas (Dalton transactions, 2011)
The neutral trigallane R3Ga3I2 was obtained in high yields by reaction of “GaI” with the moderately sterically demanding lithium N,N′-dicyclohexylneopentylamidinate. Its chemical reactions with N-lithio-2-propanimine, sodium superhydride and elemental iodine were investigated. RI-DFT calculations have been performed to confirm the bonding situation. All compounds are characterised by crystal structure analysis and NMR-spectroscopy.